116k views
1 vote
Please help me with the question thankyou ​

Please help me with the question thankyou ​-example-1
User Jorgenfb
by
4.3k points

1 Answer

6 votes

Answer:


24x^(10)

Explanation:

Key skills needed: Exponent multiplication, Multiplication

1) We have the expression -->
(4x^(3))(6x^(7))

2) We have to simplify this (the parentheses mean multiplication)

The easiest thing to do is: Multiply 4 and 6 --> 4 x 6 = 24.

3) With the step above, the expression now would be
24(x^(3))(x^7).

We now have to do
x^3 ×
x^7

For this we have to use this exponent rule -->
a^b ×
a^c =
a^(b+c).

4) This means that
x^3 ×
x^7 =
x^(3+7) = x^(10)

5) So the simplified expression would be -->
24x^(10)

Hope you understood and have a nice day!! :D

User Bruno Cloutier
by
4.9k points